2005
DOI: 10.1039/b508075d
|View full text |Cite
|
Sign up to set email alerts
|

Biofunctionalization of fluorescent-magnetic-bifunctional nanospheres and their applications

Abstract: Hydrazide-containing bifunctional nanospheres were covalently coupled on the surface with IgG, avidin, and biotin, to generate novel fluorescent-magnetic-biotargeting trifunctional nanospheres, which can be used in a number of biomedical applications, including visual sorting and manipulation of apoptotic cells as demonstrated here.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(63 citation statements)
references
References 18 publications
1
62
0
Order By: Relevance
“…As we demonstrated previously (30,31 ), the magnetic property of multifunctional nanospheres can be helpful for isolating specific cells. We used flow cytometry to obtain the fraction of apoptotic cells before and after isolation with multifunctional nanospheres to estimate the efficiency of the multifunctional nanospheres for separating apoptotic cells from living cells.…”
Section: Efficient Isolation Of Target Cells With Multifunctional Nanmentioning
confidence: 99%
See 1 more Smart Citation
“…As we demonstrated previously (30,31 ), the magnetic property of multifunctional nanospheres can be helpful for isolating specific cells. We used flow cytometry to obtain the fraction of apoptotic cells before and after isolation with multifunctional nanospheres to estimate the efficiency of the multifunctional nanospheres for separating apoptotic cells from living cells.…”
Section: Efficient Isolation Of Target Cells With Multifunctional Nanmentioning
confidence: 99%
“…A hallmark of apoptosis is the externalization of phosphatidylserine, which is recognized by annexin V. Accordingly, van Tilborg et al (35 ) and Prinzen et al (36 ) used annexin V-conjugated QDs coated with a paramagnetic lipid to detect apoptotic cells with fluorescence and magnetic resonance imaging. We recently demonstrated that trifunctional avidin-coupled nanospheres are capable of recognizing apoptotic cells preincubated with annexin V-biotin via the strong biotin-avidin interaction (31 ). To investigate the suitability of such trifunctional nanospheres for use in biomedical research, drug development, and/or diagnosis, we have conducted a detailed characterization of the properties of these trifunctional avidin-coupled nanospheres and applied them to visualizing and isolating apoptotic cells from a mixed cell population.…”
mentioning
confidence: 99%
“…Bi-functional core/shell quantum dots have been described, however combined high relaxivity for MRI and high quantum yield luminescence have not been reported for these materials. [10][11][12][13] Semiconductor nanoparticles have been exploited as optical indicators because of their narrow, tunable, symmetric emission spectrum. 3,14,15 The benefits of being able to excite with a broad excitation energy and obtain multicolored luminescence has been one of the advantages of semiconductor nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Upon exposing magnet and fluorescence microscopes, these multifunctional materials were sensitively detect and isolate target tumor cells at low concentration of 0.01% in the mixed cells. Shi et al [76] synthesized fluorescent-magnetic nanospheres by co-embedding quantum dots and magnetite nanoparticles into hydrazide-functionalized copolymer nanospheres followed by coupled on the surface with IgG, avidin and biotin to form the fluorescent-magnetic bio-targeting trifunctional nanospheres. The nanoscale biocomposites can selectively link to apoptotic cells, allowing their visualisation and isolation.…”
Section: Fluorescent-magnetic Hybrid Nanostructuresmentioning
confidence: 99%